2006
DOI: 10.1111/j.1464-410x.2006.06610.x
|View full text |Cite
|
Sign up to set email alerts
|

Urinary markers for prostate cancer

Abstract: Prostate cancer is the commonest solid‐organ malignancy to affect men in Europe and the USA; it is estimated that one in six men will develop this cancer in their lifetime. Current screening relies on a digital rectal examination with a serum prostate‐specific antigen test. Novel urinary diagnostic tests are potentially interesting screening tools for this disease. We examined published reports assessing the use of urinary markers for the diagnosis of prostate cancer. Using a PubMed‐based search we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 46 publications
0
19
0
9
Order By: Relevance
“…42,43,46 Malignancy of the urogenital tract Many nephrourological tumour-associated molecules are secreted into the urine and it is therefore not surprising that several studies have evaluated urine biomarkers for the early diagnosis and surveillance of renal cell, bladder and prostate cancer (Table 2). 47,49,53 Most of these studies have been based on small patient cohorts, and the reported sensitivity and specificity of urine biomarkers are wide ranging. With only a few studies published on each set of biomarkers, it is difficult at present to assess their potential clinical impact in the future.…”
mentioning
confidence: 99%
“…42,43,46 Malignancy of the urogenital tract Many nephrourological tumour-associated molecules are secreted into the urine and it is therefore not surprising that several studies have evaluated urine biomarkers for the early diagnosis and surveillance of renal cell, bladder and prostate cancer (Table 2). 47,49,53 Most of these studies have been based on small patient cohorts, and the reported sensitivity and specificity of urine biomarkers are wide ranging. With only a few studies published on each set of biomarkers, it is difficult at present to assess their potential clinical impact in the future.…”
mentioning
confidence: 99%
“…Almost all urine-detectable prostatespecific markers have recently been reviewed (Table 1). 7,8 For this reason, we focus here only on the promising markers which have been independently evaluated by several groups and on the very recent ones. Subsequent chapters are devoted to the current most intensively studied markers, prostate cancer antigen 3 (PCA3) and fusion genes.…”
Section: Advantages and Limitations Of Novel Urine Markersmentioning
confidence: 99%
“…Prostate cancer (PCa) is one of the most commonly diagnosed malignancies in the developed world (1). Since this disease is more common among older men, its incidence is expected to increase as the population ages.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, there are many clinical studies which evaluate biomarkers in urine (1). This type of sample represents a good fluid to seek biomarkers, mainly because it is readily available and obtained noninvasively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation